No decision about me, without me: Collaborating with young people in mental health research - Alex Lloyd; Tom (Chin‐Han) Wu; Laura Lucas; Adeola Agunbiade; Romana Saleh; Pasco Fearon; Essi Viding (JCPP Advances)
Abstract Involving young people with lived experience in youth mental health research is important. In recognition of the value of collaborating with experts by experience, international funders are increasingly mandating that mental health research is developed by teams that include individuals from the population of study. Yet, research into how Patient Public Involvement, specifically co‐production and co‐design, is implemented in youth mental health research is limited to date. The current review examined this question and identified common practices for collaborating with experts by experience in young people's mental health research. Academic databases were systematically searched for studies that had involved young people in mental health research, had described these activities, and had reported some demographic information about the experts by experience. From a total of 2130 studies that were screened, 37 studies were eligible for inclusion. The use of co‐production and co‐design spanned a wide range of topics, including interventions, digital support tools and psychometric studies. Interactive workshops were the primary method of engaging experts by experience, although some studies utilised interviews or focus groups. From the reviewed studies we identified common methodological practices including: Scene setting, utilising a cyclical process, ensuring appropriate engagement and recognition of the cultural context. We draw on these findings to suggest common methods for conducting co‐production and co‐design activities, and emphasise the importance of ensuring experts by experience are respected and safeguarded throughout their collaboration in research. We also outline areas that deserve future attention and development, and include a response from two young people aged 16–18 and their suggestions for improving and extending co‐production methods.